Performance comparison of hip fracture pathways in two capital cities: Associations with level and change of integration - Unto Häkkinen; Terje P Hagen; Tron Anders Moger (University of Oslo, 2019)
Finland and Norway have health care systems that have a varying degree of vertical integration. In Finland the financial responsibility for all patient treatment is placed at the municipal level, while in Norway the responsibility for patients is divided between the municipalities (primary and long-term care) and state-owned hospitals. From 2012, the Norwegian system became more vertically integrated following the introduction of the Coordination Reform. The aim of the paper is to analyse the associations between different modes of integration and performance indicators. The data included operated hip fracture patients from the years 2009-2014 residing in the cities of Oslo and Helsinki. Data from routinely collected national registers, also including data from primary health and long-term-care services, were linked. Performance indicators were compared at baseline (before the Coordination Reform, i.e., 2009-2011), and trends were described and analysed by difference-in-difference methods. The baseline study indicated that hip fracture patients in Oslo, compared with those in Helsinki, had longer stays in acute hospitals. They used less institutional care outside of hospitals as well as more GP services and fewer other outpatient services. Mortality was lower, and the probability of being discharged to home within 90 days from the index day was higher. After the Coordination Reform, the length of stay in hospital was shorter and the length of the first institutional episode in Oslo was longer than before the Reform, demonstrating that the shorter hospital stays were more than compensated for by longer stays in long-term-care institutions. The number of patients institutionalised 90 days from the index day increased and the number of patients discharged to home within 90 days from the index day decreased in Oslo after the Reform while the opposite trends were observed in Helsinki. After the Reform, the performance differences between the two regions had decreased.   Published: Online December 2018. In print January 2019.